Urban Sustainability Concepts in Reconstruction Projects of Damaged Cities (The City of Basra as a Model) - Al-Musaed, Dr. Amjad (Basrah Journal for Engineering Sciences, 2015)
Wars have imposed on some countries a state of haste and rush towards haphazard, unstudied urban planning to fill the shortage of architectural elements and urban formations. Urban sustainability, alongside environmental and economic sustainability, has recently gained great importance in contemporary global studies. Given the problems suffered by the city of Basra regarding architectural formation and devastating environmental pollution, in addition to the significant deficit in finding the required design solutions for the urban rehabilitation of the city, it was necessary to limit individual attempts that tend towards unconscious concepts leading to anomaly and lack of harmony with the city's distinct environment. Urban formation is a series of visual interferences that cannot be intercepted by individual, personal, and unstudied attempts; therefore, shared visions agreed upon by specialists in various fields, primarily the environment, must be formulated. Hence, the research tends towards finding research areas that can offer objective and realistic solutions to be the basis for the future structure of damaged cities within the framework of the concept of sustainable urban development in the future. Here, the research aims to select the best methods for shaping the modern city of Basra.